Edge-dependent interpolation-based deinterlacing using edge patterns - Park, Min Kyu; Byun, Min; Park, Jong Hyun; Kang, Moon Gi (Journal of electronic imaging, 2006)
A deinterlacing algorithm based on edge-dependent interpolation (EDI) that considers edge patterns is proposed. Generally, EDI algorithms perform visually better than other deinterlacing algorithms using one field. However, they produce unpleasant results due to failure in estimating edge direction. To estimate the edge direction precisely, not only simple differences between adjacent two lines but also edge patterns are used. Edge patterns, which give sufficient information to estimate the edge direction, appear along the edge direction. Therefore, we analyze properties of edge patterns and model them as a weight function. The weight function helps the proposed method to estimate the edge direction precisely. Experimental results indicate that the proposed algorithm outperforms conventional EDI approaches with respect to both objective and subjective criteria.